The high-Andean Jivarus Giglio-Tos (Orthoptera, Acridoidea, Melanoplinae): Systematics, phylogenetic and biogeographic considerations - Cigliano, María Marta (2010)
The high-Andean genus Jivarus Giglio-Tos from Ecuador, Colombia and Peru is revised. Morphological cladistic analysis indicated that Jivarus montanus and the new species digiticercus. sp.n. and rugosus. sp.n. must be treated as a separate genus, Maylasacris gen.n. The remaining species included in the analysis are assigned to the genus Jivarus, for which the following six species groups are identified: americanus group, antisanae group, carbonelli group, cohni group, pictifrons group and jagoi group. Twenty-nine species are recognized for Jivarus, with ten described as new: J. rectus. sp.n., J. megacercus sp.n., J. spatulus. sp.n., J. auriculus. sp.n., J. riveti. sp.n., J. sphaericus. sp.n., J. discoloris. sp.n., J. profundus. sp.n., J. ronderosi. sp.n. and J. guarandaensis. sp.n. The following new synonymies are proposed: Jivarus albolineatus Ronderos with J. antisanae (Bolivar) syn.n., J. cerdai Ronderos and J. osunai Ronderos with J. alienus (Walker) syn.n., and J. rubriventris Ronderos with J. ecuadorica (Hebard) syn.n.; the new combinations Jivarus ecuadorica (Ronderos) comb.n. and Maylasacris montanus (Ronderos) comb.n. are proposed. Keys to the species of the genera and a review of the morphological characters defining the taxa are provided. Patterns of distribution of the clades coincide with the geography of the northern Andes of Colombia and Ecuador. Areas of endemism of the Jivarus species groups and Maylasacris are delimited by both the high-altitude curves, including transverse zones, and the drier climates of the intra-Andean valleys, clearly indicating recent, post-glacial palaeogeography, as shown also in vegetation distributions. This paper has been formatted with many embedded links to images of type and paratype specimens, maps based on geo-referenced specimen data and species keys available on the Orthoptera Species file online (http://orthoptera.speciesfile.org).